Yield and quality of intercropped wheat in jujube‐ and walnut‐based agroforestry systems in southern Xinjiang Province, China. (12th June 2020) - Qiao, Xu; Xiao, Li; Gao, Yonghong; Zhang, Wen; Chen, Xingwu; Sai, Lihan; Lei, Junjie; Xue, Lihua; Zhang, Yongqiang; Li, Ailian
Abstract: Agroforestry is widely practiced in China and has the benefit of diversifying agricultural production and enhancing natural resource utilization; however, these systems create competition for light between trees and understory crops. We investigated the effects of shading by jujube ( Zizyphus jujuba Mill.) and walnut ( Juglans regia L.) trees on the yield and quality of intercropped wheat ( Triticum aestivum L.) in agroforestry systems in southern Xinjiang Province, China. In the walnut–wheat intercropping system, mean daily photosynthetically active radiation (PAR) and net photosynthetic rates (Pn) in the understory were reduced by 72.4–79.7% and 45.8–49.6%, respectively, at the grain‐filling stage as compared to wheat grown in monoculture. Relative to monoculture wheat, the walnut‐based system resulted in significant reductions in the number of florets and spikelets per spike, grain‐filling rate, and grain yield and its components in intercropped wheat. In contrast, N and P concentrations, and protein and wet gluten contents of intercropped wheat were significantly increase. In the jujube–wheat intercropping system, mean daily PAR and Pn in the understory were reduced by 23.2–25.5% and 27.2–34.3% at the grain‐filling stage compared to monoculture wheat, but grain yield and its components, the number of florets and spikelets, N and P concentrations, and protein and wet gluten contents of wheat did not differ between the two systems. The jujube‐based agroforestry system was more sustainable than the walnut‐based system in our study region, but competition for light between walnut trees and intercrops may be alleviated by selective felling, pruning, and wider tree spacing.